2011
DOI: 10.1075/sll.14.1.06lew
|View full text |Cite
|
Sign up to set email alerts
|

Mouth gestures in British Sign Language

Abstract: This article investigates the claim that tongue protrusion ('th') acts as a nonmanual adverbial morpheme in British Sign Language (BSL) (Brennan 1992; SuttonSpence & Woll 1999) drawing on narrative data produced by two deaf native signers as part of the European Cultural Heritage Online (ECHO) corpus. Data from ten BSL narratives have been analysed to observe the frequency and form of tongue protrusion. The results from this preliminary investigation indicate tongue protrusion occurs as part of the phonologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…While the use of oral adverbials has been well-described for languages like ASL (e.g. Liddell, 1980) and recently for BSL (Lewin & Schembri, 2011), the alternate use of mouthings and mouth gestures accompanying nouns and adjectives is a new finding that demands further investigation. While some of the adjectives in our study might be analysed as adjectival predicates, at first sight, a verbal function does not appear to apply to the noun GROUP in NGT.…”
Section: Conclusion 251 General Conclusionmentioning
confidence: 99%
“…While the use of oral adverbials has been well-described for languages like ASL (e.g. Liddell, 1980) and recently for BSL (Lewin & Schembri, 2011), the alternate use of mouthings and mouth gestures accompanying nouns and adjectives is a new finding that demands further investigation. While some of the adjectives in our study might be analysed as adjectival predicates, at first sight, a verbal function does not appear to apply to the noun GROUP in NGT.…”
Section: Conclusion 251 General Conclusionmentioning
confidence: 99%
“…If echoes are involuntary motor couplings of two or more articulators, we would expect them to be obligatory and far more widespread than they are, but if they serve linguistic purposes such as enhancing the phonetic signal, there is no reason to assume that echoes are obligatory components of signs. In fact, some scholars suggest that optional mouth articulations are, indeed, echoes; Lewin and Schembri (2011) characterize British SL FALSE and NOTHING as having optional echoes, and Fontana (2008) claims an optional mouth echo for Italian SL DO-NOT-REALIZE. Further, a note on iconicity is necessary. Woll distinguishes echo articulations from enactments, in which the nonmanual action corresponds to a part of the denotation of the sign.…”
Section: A Note On Obligatoriness and Iconicitymentioning
confidence: 99%
“…Earlier studies, including studies on STS, have suggested that mouthing appears with nouns or noun phrases, "uninflected" verb forms, open-class items, and "morphologically simple" signs (Bergman & Wallin 2001;Crasborn et al 2008;Lewin & Schembri 2011). Given this background, and since STSC-L2 includes annotations for grammatical class, we present some frequency and distribution data for this analysis based on those mouthings which are used most frequently (i.e., M-type, ME-type).…”
Section: Grammatical Classmentioning
confidence: 99%